AB0922 Disease activity assessment in ankylosing spondylitis: Basdai or asdas?. (23rd January 2014) - Au, Y.L.E.; Wong, W.S.R.; Mok, M.Y.; Chung, H.Y.; Chan, E.; Lau, C.S.
Abstract : Background: Recently, a new index, the Ankylosing Spondylitis Disease activity Score (ASDAS), has been shown to be a validated and highly discriminatory instrument in assessing disease activity. Objectives: To evaluate the performance of ASDAS in a local Chinese cohort of Ankylosing Spondylitis (AS) in a cross- sectional setting, and to compare it with the existing instrument, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) Methods: Consecutive patients with AS were recruited from a local rheumatology clinic. The discriminatory capacity of BASDAI and ASDAS was compared by: (1) standardized mean difference statistics, (2) R-squared in linear regressions, and (3) Area under receiver operating characteristic curve (AUC) in logistic regression models. Results: One hundred and sixty-five AS patients were included in the study, with 123 males and 42 females. The mean age of the subjects was 44 years and the median duration of illness was 11 years. Both BASDAI and ASDAS C showed satisfactory and comparable results in our study, with R 2 of 0.65 and 0.64 respectively in relation to patient global assessment score, and 0.57 in relation to physician global assessment score.Both indices also demonstrated good discriminatory capacity as evidenced by a high AUC (>0.9) under the logistic regression models using either patient or physicisn global assessment score >6 and <4 as cut off of high and low disease activity status respectively. Although we could not demonstrate significant differences in the performance between them, subgroup analysis suggests better discriminatory ability of ASDAS in the high inflammatory marker subgroup. In the subgroup of patients with high inflammatory markers, standardized mean difference (SMD) of ASDAS C was 3.20 (CI 2.29-4.12) and that of BASDAI was 2.65 (CI 1.82-3.49). On the other hand, in cases of low inflammatory markers, the performance of both indices was comparable, with BASDAI achieving slightly better results (SMD of BASDAI was 3.74; CI 2.91-4.58 and SMD of ASDAS C was 3.64; 2.82-4.46). Conclusions: ASDAS and BASDAI showed similarly good performance in a cross sectional setting in a local Chinese AS cohort. ASDAS performed better in subgroup with raised inflammatory markers. References: Calin A, Nakache JP, Gueguen A, Zeidler H, Mielants H, Dougados M. Defining disease activity in ankylosing spondylitis: is a combination of variables (Bath Ankylosing Spondylitis Disease Activity Index) an appropriate instrument? Rheumatology (Oxford). 1999 Sep;38(9):878-82. Lukas C, Landewe R, Sieper J, Dougados M, Davis J, Braun J, et al. Development of an ASAS-endorsed disease activity score (ASDAS) in patients with ankylosing spondylitis. Ann Rheum Dis. 2009 Jan;68(1):18-24. van der Heijde D, Lie E, Kvien TK, Sieper J, Van den Bosch F, Listing J, et al. ASDAS, a highly discriminatory ASAS-endorsed disease activity score in patients with ankylosing spondylitis. Ann Rheum Dis. 2009 Dec;68(12):1811-8. Disclosure of Interest: None Declared